Pemanfaatan Bambu sebagai Industri Kreatif “Anyaman Peralatan Rumah Tangga” Guna Meningkatkan Perekonomian Lokal - Dedy Khaerudin; Irma Nurmala Dewi; Asep Sapaatullah; Ganjar Sidik Gandara; Khaeruzzaman Khaeruzzaman; Silvi Alpiani (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Mekarsari Village, located in Panimbang District, Pandeglang Regency, Banten Province, has local potential in the form of a bamboo-based home industry. This potential has long been part of the cultural and economic identity of the local community. Therefore, the goal of this Community Service (PKM) activity is to increase the income of bamboo craftsmen by encouraging innovation, improving product quality, and broader marketing strategies. The PKM activity was carried out by male and female students of KKM Universitas Bina Bangsa, group 41 of 2025. The stages of activities carried out in this program include three main phases. The pre-implementation stage was carried out through a process of observation and direct visits to the homes of bamboo craftsmen in Sumur Kuya Village, Mekarsari Village. Students conducted short interviews to explore obstacles and potential in production activities carried out so far. The implementation stage included practical work on making household products such as winnowing baskets, food covers, tissue holders, and bamboo baskets by KKM41 participants, guided directly by the craftsmen. Students also provided light training on product design to make it more attractive and competitive in the market. The final stage, the evaluation stage, was conducted through product socialization activities to the local community, including mini-exhibitions and open discussions. The community was educated on the importance of preserving local heritage while remaining open to innovation in production and marketing. This activity was held from July 18–20, 2025. The methods used included observation, field surveys, interviews, and hands-on practice. Bamboo was chosen as the basic material because it is abundant in the surrounding environment, as well as its advantages as an environmentally friendly material with high aesthetic value.